The identification of students abductive types in science learning using an abductive inquiry model with connected integration type - N Nuriyanti; R Ramalis; s Supriatna (Pascasarjana Universitas Pendidikan Indonesia, 2020)
In recent years, there has been an increasing interest in student thinking skills. Many researchers argue that reasoning skills are one of the most important skills for the students, one of which is abductive reasoning. Therefore, the study aims at identifying various students' abductive types in science learning by applying the integrated type of abductive inquiry learning model on global warming topic. This research was a qualitative study, utilizing an audio recording of student and teacher dialogues during learning and an observation sheet. The subjects in this study were 30 students of grade VII selected by convenience sampling technique. The results showed that the abductive types of students in learning science varied between groups. These types included theoretical abductive, existential abductive and legal or regulatory abductive.